Differentiated Instruction Strategies in Inclusive Classes for Students with Learning Disabilities - Chitorelidze, Tinatin; Bartoňová, Miroslava, 1965-; Masarykova univerzita. Katedra speciální pedagogiky (2017)
Školy jsou vystavené problémům pramenícím z diversity žáků a z různorodosti jejich potřeb. Pro úspěšnou implementaci inkluze je klíčový také postoj vedení školy, role učitelů, intenzivní spolupráce učitelů s dalšími odborníky a detailní plánování učebního procesu. Učitelé, kteří uplatňují diferenciaci instrukcí naplňují různorodé akademické potřeby všech žáků. Vnímání diverzity zvyšuje pravděpodobnost efektivní výuky a umožňuje učiteli plánovat s různými přístupy k tomu, co by se žák měl naučit, jak ho to naučit a jak vyjádřit, co se již žák naučil a čemu porozuměl. Cílem studie bylo analyzovat vnímání inkluze učiteli a prozkoumat praxi diferencovaných učebních metod a faktorů, které usnadňují nebo brání její implementaci. Analýza dat odhalila řadu strategií používaných ve výuce žáků s potížemi v učení. Byly také zdůrazněné hlavní překážky celého procesu a diskutována možná řešení. V závěru práce byla představená doporučení pro zlepšení procesu implementace diferenciace instrukcí.
The schools are facing difficulties, which are caused by students' diversity and their differing needs. For the successful implementation of the inclusion the attitude of the administration is crucial, especially the role of teachers, as well as the, intensive cooperation between teachers and other professionals, and the detailed planning of the teaching process. Those teachers who use differentiated teaching methods meet the diverse academic needs of all students. Perception of diversity increases the likelihood of effective teaching and allows the teacher to plan with different approachs: what the students should learn, how to learn, and how to express what they have learned and understood. The study aimed to investigate teachers perceptions and practices of differentiated teaching methods, and the factors that helps or hinders its implementation. The data analysis revealed the set of teaching strategies, used for accommodating students with learning disabilities. Major hindrances in
Vedoucí práce: Miroslava Bartoňová
Dizertace (Ph.D.)--Masarykova univerzita, Pedagogická fakulta, 2017
Keywords: diferencovaná výuka; integrovaná výchova a vzdělávání; klíčové kompetence; pedagogické dovednosti; specifické poruchy učení; vyučovací metody; differentiated education; integrated education; key competencies; learning disabilities; teaching methods; teaching skills; disertace; dissertations